Pengaruh konsentrasi gula terhadap aktivitas antioksidan pada minuman bir pletok - Dyah Permanasari; Afrinia Eka Sari; Mujahidil Aslam (AcTion: Aceh Nutrition Journal, 2021)
Pletok beer is a spice drink originating from the Betawi tribe. Spices used in pletok brewing include ginger, cloves, lemongrass, cinnamon, secang.  This research aims to formulate Bir Pletok which produces high antioxidant activity and high acceptance from panelists. Bir Pletok formulated in the form of a variety sugar concentration, that is 4%, 8%, 12%. This research will be examined the antioxidant activity and the sensory analysis of Bir Pletok to find out the panelists’ acceptance of its color, smell, and taste. This research will be conducted at STIKes Mitra Keluarga with 30 panelists. This research uses the experimental Descriptive method. The independent variable in this research is the sugar concentration, while the dependent variable is the antioxidant activity. Measurement of the antioxidant activity will use the DPPH test and the hedonic (preference) test using questionnaires. The results showed that the combination treatment of the addition of sugar equal to 4% is the best results: Antioxidant Capacity 610,278 ppm and a panelist as well as the colors 3,83 (like), odor 3,86 (Like); and sense at 2,86 (Neutral). Overall, the Bir pletok had high antioxidant activity that is the potential to prevent non-communicable diseases. important factors in the pletok brewing process are heating time and temperature.